RealiseNothing
what is that?It is Cowpea
c) iii) This is just an integration by parts, I won't go through most of the working out as it is just straight forward IBP. However:
![](https://latex.codecogs.com/png.latex?\bg_white I_{2n-1} = \lim_{a \to 0} \int_{a}^{\pi} \frac{x}{2} \frac{\sin(\frac{(4n-1)x}{2})}{\sin(\frac{x}{2})} dx)
Let
and thus
(given)
Let
and thus ![](https://latex.codecogs.com/png.latex?\bg_white v = \frac{-cos(\frac{(4n-1)x}{2})}{\frac{(4n-1)}{2}})
Put these into the IBP formula and evaluate the
, then factor out
to obtain the result of:
![](https://latex.codecogs.com/png.latex?\bg_white I_{2n-1} = \frac{2}{(4n-1)}[1+ \lim_{a \to 0} \int_{a}^{\pi} g(x) \cos(\frac{(4n-1)x}{2}) dx])
c)iv) Now we know that
, hence we can deduce that:
![](https://latex.codecogs.com/png.latex?\bg_white \lim_{a \to 0} \int_{a}^{\pi} -g(x) dx \leq \lim_{a \to 0} \int_{a}^{\pi} g(x) \cos(\frac{(4n-1)x}{2}) dx \leq \lim_{a \to 0} \int_{a}^{\pi} -g(x) dx)
Evaluating the upper and lower bounds gives:
![](https://latex.codecogs.com/png.latex?\bg_white [\frac{\frac{-x}{2}}{\sin(\frac{x}{2})}] \leq \lim_{a \to 0} \int_{a}^{\pi} g(x) \cos(\frac{(4n-1)x}{2}) dx \leq [\frac{\frac{x}{2}}{\sin(\frac{x}{2})}])
Now we know that
so we evaluate using the limits and we get the required result:
![](https://latex.codecogs.com/png.latex?\bg_white 1 - \frac{\pi}{2} \leq \lim_{a \to 0} \int_{a}^{\pi} g(x) \cos(\frac{(4n-1)x}{2}) dx \leq \frac{\pi}{2} - 1)
c)v) As
we get
.
Now as we established above,
is a finite as it is bounded between two finite values.
Thus![](https://latex.codecogs.com/png.latex?\bg_white I_{2n-1} \to 0)
c)vi) We know now that as
we get
and so from part c)ii) we get:
![](https://latex.codecogs.com/png.latex?\bg_white lim_{n \to \infty} \sum_{k=1}^{n} \frac{1}{(2k-1)^2} = \frac{\pi^2}{8})
Also we have:
![](https://latex.codecogs.com/png.latex?\bg_white \sum_{k=1}^{\infty} \frac{1}{k^2} = {\sum_{k=1}^{\infty} \frac{1}{(2k-1)^2}} + \sum_{k=1}^{\infty} \frac{1}{(2k)^2})
Substituting in our known value for the sum of the reciprocal odd squares, and factorising out a quarter from the last summation gives:
![](https://latex.codecogs.com/png.latex?\bg_white \sum_{k=1}^{\infty} \frac{1}{k^2} = \frac{\pi^2}{8} + \frac{1}{4} \sum_{k=1}^{\infty} \frac{1}{k^2})
![](https://latex.codecogs.com/png.latex?\bg_white \frac{3}{4} \sum_{k=1}^{\infty} \frac{1}{k^2} = \frac{\pi^2}{8})
![](https://latex.codecogs.com/png.latex?\bg_white \sum_{k=1}^{\infty} \frac{1}{k^2} = \frac{\pi^2}{6})
Let
Let
Put these into the IBP formula and evaluate the
c)iv) Now we know that
Evaluating the upper and lower bounds gives:
Now we know that
c)v) As
Now as we established above,
Thus
c)vi) We know now that as
Also we have:
Substituting in our known value for the sum of the reciprocal odd squares, and factorising out a quarter from the last summation gives:
Last edited: